Fertility issues among pediatric oncology patients - short communication - Vlad Dima; Roxana-Elena Bohitea; Adrian Ioan Toma; Roxana Georgiana Bors; Valentin-Nicolae Varlas; Ana-Maria Davitoiu (Amaltea Medical Publishing House, 2023)
Childhood cancer survival rates are constantly improving due to treatment. Fertility research has focused on adult cancer patients, but studies among childhood cancer survivors who reach reproductive age are rare and mainly based on small numbers of patients. This is surprising as childhood cancer survivors constitute a distinct, ever-growing population that may have temporarily or permanently impaired fertility due to cancer treatment. Thus, the basic scientific concern specific to the pediatric population has focused on improving protection techniques and cryopreserved tissue transfer. Research on preservation techniques confirms the safety of surgical retrieval of gonadal (ovarian and testicular) tissue for cryopreservation. Outcomes may improve, but it is clear that large registries of long-term follow-up of patients are needed. Current research efforts imply the need to develop a national strategy in each country to ensure the education and information of pediatric patients undergoing gonadotoxic regimens and their families about fertility options and subsequent outcomes and give them the opportunity to join such programs.